Pengaruh Media Mystery Box Terhadap Kemampuan Menulis Karangan Deskripsi Siswa Kelas IV UPTD SDN 32 Barru - Tappareng, Andi; Bahri, Aliem; Rahayu, Sri (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
The main problem in this research is that learning activities are still focused on the teacher, students lack focus in learning and often complain of being bored in learning, resulting in low ability to write descriptive essays. This research aims to determine the effect of Mystery Box media on the ability to write descriptive essays for the IVUPTD SDN 32 Barru class. This type of research is Quasi Experimental Design research and is a quantitative type of research. The sample in this study was 25 students. Data collection techniques were carried out using learning results tests and observation sheets. The data analysis technique in this research is descriptive data analysis technique and T-Test. The research results showed that the ability to write descriptive essays before implementing the Mystery Box media in the pretest had an average score of 57. Meanwhile, in the posttest there was a change with an average score of 81. The results of the t-test analysis of the influence of the Mystery Box media on the learning outcomes of student participants showed that The result shows that the significance value obtained is good, namely the influence of the Mystery Box media on the ability to write descriptive essays (Sig = 0.013) is smaller than the alpha value set, namely 0.05 (0.019 < 0.03). Based on the results obtained, it can be concluded that Ho is rejected and H1 is accepted, which states that there is an influence of the Mystery Box media on the ability to write descriptive essays of class IV students at UPTD SDN 32 Barru.